A history about teachers’ formation in Brazil: A bibliographical study (Research, Society and Development, 2021)
After Brazilian Independence, the first contexts about teachers’ formation appear in the country. The theme, still widely discussed, suffer alterations on each modification or implementation of public policies. Thus, this article aims to briefly point out the historicity of the formative processes of teachers in the Brazilian context from 1827 to the current days. By performing a bibliographical result on the most prominent authors in the field  and the documents that rule the Brazilian legislation, to discuss the six periods pointed out by Demerval Saviani and by the current context about the teachers’ formation presented on the National Common Curricular Base (BRASIL, 2019). It was verified a new vision about teachers’ formation, which prioritizes the practical context of the profession instead of the theoretical one. It was also verified the lack of dialogue in the public policies, where researchers in the area of formation were a little or no listened, causing gaps and shards on teachers’ formation.